1994
DOI: 10.1080/15321819408009577
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Free Insulin-Like Growth Factor-I Using Immunoradiometric Assay

Abstract: The free Insulin-like growth factor-I (IGF-I) in plasma from normal adults was directly measured with a newly developed highly sensitive immunoradiometric assay (IRMA) for IGF-I. The capture antibody did not crossreact with IGF-I associated binding proteins which exist in plasma, and the assay was designed not to shift the equilibrium of the IGF-I and binding proteins. Total IGF-I concentration was measured using this assay with preliminary acid-ethanol extraction. Approximately 1 percent of total IGF-I existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 11 publications
2
27
1
Order By: Relevance
“…In this study of healthy adult subjects, we found acute changes in the IGF-I system involving not only IGFBP-1, but also IGFBP-3 and free IGF-I. Basal values for these parameters were similar to those reported by others (4,10,(15)(16)(17). We used a single injection of insulin after an iv bolus of glucose that triggered a physiological insulin release, and we obtained a well characterized blood glucose pattern with an early peak and a nadir by 60 min followed by a rapid recovery (11).…”
Section: Discussionsupporting
confidence: 72%
“…In this study of healthy adult subjects, we found acute changes in the IGF-I system involving not only IGFBP-1, but also IGFBP-3 and free IGF-I. Basal values for these parameters were similar to those reported by others (4,10,(15)(16)(17). We used a single injection of insulin after an iv bolus of glucose that triggered a physiological insulin release, and we obtained a well characterized blood glucose pattern with an early peak and a nadir by 60 min followed by a rapid recovery (11).…”
Section: Discussionsupporting
confidence: 72%
“…Hizuka et al reported that free IGF-I levels increased during pregnancy [18]. Recently, an increase in the free IGF-I level in pregnant women, determined by a newly developed immunoradiometric assay, was also reported by our group [19,20]. It is therefore important to check the proteolytic activity in sera to understand the action of IGFs in various physiological conditions.…”
Section: 8=476%)mentioning
confidence: 99%
“…Biological potency of serum GH was determined using an Nb2 cell-proliferation assay, as described previously [14]. Serum total and free IGF-1 were measured by an immunoradiometric assay (IRMA) (Chiba-Corning, Tokyo) [15]. Serum IGFBP-3 was measured by the RIA method [16, 17][Diagnostic Systems Laboratories (DSL), Tokyo].…”
Section: Methodsmentioning
confidence: 99%